Co-pyrolysis and combustion characteristics of polylactic acid and acrylonitrile-butadiene-styrene: insights into interactions, kinetics and synergistic effects - Xujuan Wu; Yunpeng Yang; Yuanyuan Zhan; Kaiyuan Li; Fei Xiao (Frontiers in Chemistry)
Polylactic acid (PLA) and acrylonitrile-butadiene-styrene (ABS) are the most commonly used filaments in 3D printing. To enable filament materials to withstand higher stresses, PLA and ABS are often blended (PLA/ABS). In this work, the co-pyrolysis and combustion properties of PLA/ABS blends of various ratios (75%/25%, 50%/50%, and 25%/75%) were analyzed. Thermogravimetric analysis showed that the catalytic pyrolysis of the blends became more intense as the proportion of PLA in PLA/ABS increased. Cone calorimetry tests indicated that the pyrolysis of ABS determines the peak heat release rate of the PLA/ABS blend. The higher amount of PLA allows the blend to pyrolyze at lower temperatures and the combustion reaction becomes more violent. The theoretical heat of combustion was calculated by correlating the average and maximum HRR with the heat flux through theoretical analysis. The theoretical heat of combustion obtained from the maximum HRR data is more reliable than from the average HRR data. This study has implications for the efficient utilization and fire protection of materials based on PLA/ABS.